A negative electrode sheet and preparation method thereof and secondary battery

By setting up a multi-layer structure on the negative electrode sheet of the lithium-ion battery, using the combination of silicon material and gas-producing material, the problems of expansion and capacity attenuation of silicon negative electrode materials in lithium-ion batteries are solved, and higher cycle stability and capacity are achieved Retention rate.

CN115295764BActive Publication Date: 2024-12-17JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210907036.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2024-12-17
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

The silicon negative electrode material in lithium-ion batteries has volume expansion and inherent problems during the lithiation process, resulting in poor electronic conductivity and uncontrollable secondary growth of solid electrolyte interfaces, destroying battery integrity, and thus rapidly attenuating capacity.

Method used

A negative electrode sheet is adopted, including a diaphragm layer arranged on the negative electrode current collector. The diaphragm layer is composed of silicon material, gas-producing material, adhesive and conductive agent, and is a multi-layer structure of an expansion layer, a buffer layer and a protective layer. , controls the expansion and porosity of the electrode material and improves cycling stability.

Benefits of technology

Effectively slow down the expansion of electrode materials during circulation, control capacity attenuation, improve cycle stability and capacity retention, and extend the service life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115295764B_ABST
    Figure CN115295764B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary batteries, and in particular, relates to a negative electrode plate and a secondary battery. The negative electrode plate of the present invention includes a negative electrode current collector and a membrane layer disposed on at least one surface of the negative electrode current collector, and the membrane layer includes the following raw materials in parts by weight: 80 to 98 parts of silicon material, 0.1 to 5 parts of gas generating material, 1 to 10 parts of binder and 0.2 to 8 parts of conductive agent. A negative electrode plate of the present invention can effectively control the expansion of electrode materials during the cycle, control capacity attenuation, and improve cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode plate and a preparation method thereof, and a secondary battery. Background Art

[0002] Currently, lithium-ion batteries (LIBs) are widely used in portable devices and electronic products. However, there are still some problems in the application of electric vehicles and renewable energy storage grids, including energy density, material cost and safety of use. Therefore, it is very important to develop lithium-ion batteries with high energy density and long cycle life.

[0003] Silicon (Si) has been developed as an attractive candidate for negative electrode materials due to its excellent theoretical specific surface area capacity. Silicon anodes have a high theoretical capacity (about 4200 mAh / g), which is about 10 times the capacity of currently available commercial graphite anodes (about 370 mAh / g). Unfortunately, silicon has serious inherent problems during the lithiation / delithiation process. Repeated insertion and extraction of lithium ions can easily cause huge volume changes (about 300%) and ruptures, resulting in poor electronic conductivity and uncontrollable secondary growth of solid electrolyte interface (SEI) films, which will eventually destroy the integrity of the battery and cause rapid capacity decay.

[0004] Carbon-coated silicon is an effective strategy to inhibit the volume expansion of silicon anode materials in lithium-ion batteries and improve cycle stability. However, optimizing the structure of carbon / silicon coating materials and improving the structural stability and flexibility at the anode sheet level remain huge challenges. Summary of the invention

[0005] One of the purposes of the present invention is to provide a negative electrode plate to address the deficiencies of the prior art, which can effectively control the expansion of the electrode material during the cycle, control the capacity decay, and improve the cycle stability.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A negative electrode plate comprises a negative electrode current collector and a membrane layer arranged on at least one surface of the negative electrode current collector, wherein the membrane layer comprises the following raw materials in parts by weight: 80 to 98 parts of silicon material, 0.1 to 5 parts of gas generating material, 1 to 10 parts of binder and 0.2 to 8 parts of conductive agent.

[0008] Preferably, the membrane layer comprises an expansion layer disposed on the surface of the negative electrode current collector, a buffer layer disposed on a side of the expansion layer away from the negative electrode current collector, and a protective layer disposed on a side of the buffer layer away from the expansion layer.

[0009] Preferably, the thickness of the membrane layer is 0.035-0.95 mm, and the compaction density of the membrane layer is 1.05-1.90 g / cm 3 .

[0010] Preferably, the pore diameters of the expansion layer, the buffer layer and the protective layer satisfy the following relationship: K 膨胀层50 ≥K 缓冲层50 ≥K 保护层50 , K 膨胀层50 ≤0.035mm, K 保护层50 >0.

[0011] Preferably, the mass proportion of silicon material in the expansion layer, buffer layer and protective layer is 80% to 98%, the mass proportion of gas-generating material in the expansion layer, buffer layer and protective layer is 0.1% to 5%, the mass proportion of binder in the expansion layer, buffer layer and protective layer is 1% to 10%, and the mass proportion of conductive agent in the expansion layer, buffer layer and protective layer is 0.2% to 8%.

[0012] Preferably, the silicon material content in the expansion layer is greater than that in the buffer layer, and the silicon material content in the buffer layer is greater than that in the protective layer.

[0013] Preferably, the content of the gas generating material in the expansion layer is greater than that in the buffer layer and / or the content of the gas generating material in the expansion layer is greater than that in the protective layer.

[0014] Preferably, the binder content in the expansion layer is greater than the binder content in the buffer layer and / or the binder content in the protective layer is greater than the binder content in the buffer layer.

[0015] Preferably, the content of the conductive agent in the expansion layer is greater than that in the buffer layer and / or the content of the conductive agent in the expansion layer is greater than that in the protective layer.

[0016] The second purpose of the present invention is to provide a method for preparing a negative electrode plate in view of the shortcomings of the prior art, prepare slurries with different silicon material contents and gas-generating material contents respectively, and obtain an expansion layer, a buffer layer and a protective layer respectively after coating, and the preparation method is convenient and efficient.

[0017] In order to achieve the above object, the present invention adopts the following technical solutions:

[0018] A method for preparing a negative electrode sheet comprises the following steps:

[0019] Step S1, mixing silicon material, gas generating material, binder and conductive agent in a first ratio, adding solvent and stirring to obtain a first negative electrode slurry;

[0020] Step S2, coating the first negative electrode slurry on at least one surface of the negative electrode current collector, and drying to form an expansion layer; Step S3, mixing the silicon material, the gas generating material, the binder and the conductive agent according to a second ratio, adding a solvent and stirring to obtain a second negative electrode slurry;

[0021] Step S4, coating the second negative electrode slurry on the surface of the expansion layer and drying to form a buffer layer;

[0022] Step S5, mixing the silicon material, the gas generating material, the binder and the conductive agent in a third ratio, adding a solvent and stirring to obtain a third negative electrode slurry;

[0023] Step S6: coating the third negative electrode slurry on the surface of the buffer layer, drying to form a protective layer, and obtaining a negative electrode sheet.

[0024] The third object of the present invention is to provide a secondary battery with higher capacity and cycle life, slower capacity decay and better cycle stability in view of the deficiencies in the prior art.

[0025] In order to achieve the above object, the present invention adopts the following technical solutions:

[0026] A secondary battery comprises the above-mentioned negative electrode plate.

[0027] Compared with the prior art, the beneficial effect of the present invention is that the present invention arranges silicon material in the electrode to increase the capacity and also adds gas-generating material, so that the electrode has a certain porosity, provides space for the volume expansion of the silicon material, effectively slows down the expansion of the electrode material during the cycle, and also controls the capacity attenuation and improves the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic structural diagram of the negative electrode plate of the present invention.

[0029] Among them: 1. negative electrode current collector; 2. membrane layer; 21. expansion layer; 22. buffer layer; 23. protective layer; 24. pores; 25. silicon material. DETAILED DESCRIPTION

[0030] The present invention will be described in further detail below in conjunction with specific implementation modes and the accompanying drawings, but the implementation modes of the present invention are not limited thereto.

[0031] 1. A negative electrode sheet that can effectively control the expansion of electrode materials during the cycle, control capacity attenuation, and improve cycle stability.

[0032] A negative electrode plate comprises a negative electrode current collector 1 and a membrane layer 2 arranged on at least one surface of the negative electrode current collector 1, wherein the membrane layer 2 comprises the following raw materials in parts by weight: 80 to 98 parts of silicon material 25, 0.1 to 5 parts of gas generating material, 1 to 10 parts of binder and 0.2 to 8 parts of conductive agent.

[0033] The present invention arranges silicon material 25 in the electrode to increase the capacity and also adds gas-generating material, so that the electrode has a certain porosity 24, provides space for the volume expansion of the silicon material 25, effectively slows down the expansion of the electrode material during the cycle, and also controls the capacity attenuation and improves the cycle stability.

[0034] The silicon material 25 contains at least one of carbon-coated nano- or micro-silicon material 25, nano- or micro-silicon oxide and carbon composite material, silicon-carbon nano- or micro-wire material, and SiOx (2>x>0) carbon nano- or micro-composite material; further, the silicon material 25 contains at least one of artificial graphite, natural graphite, modified graphite, soft carbon, and hard carbon; further, the silicon material 25 also contains at least one element of oxygen, lithium, magnesium, sodium, potassium, calcium, beryllium, strontium, zirconium, vanadium, boron, zinc, aluminum, silver, and fluorine. The silicon material 25 can be a single particle or a composite particle; further, the composite particle is obtained by polymerizing multiple single particles.

[0035] The gas generating material is at least one of ammonium fluoride, ammonium chloride and ammonium nitrate.

[0036] The binder is at least one of monomers, polymers and copolymers of acrylonitrile, vinylidene fluoride, sodium carboxymethyl cellulose, methacryloyl, acrylic acid, pamine, acrylamide, amide, imide, acrylate, styrene-butadiene rubber, vinyl alcohol, sodium alginate, chitosan, ethylene glycol and the like.

[0037] The conductive agent is at least one of conductive carbon black, acetylene black, graphite, graphene, micro-nano fibrous conductive agent, and micro-nano tubular conductive agent.

[0038] The negative electrode current collector 1 is at least one of copper foil, porous copper foil, foam nickel / copper foil, galvanized copper foil, nickel-plated copper foil, carbon-coated copper foil, nickel foil, titanium foil, carbon-containing porous copper foil, single metal or multi-metal porous copper foil, preferably copper foil, galvanized, nickel-plated copper foil, carbon-coated copper foil.

[0039] In some embodiments, the membrane layer 2 includes an expansion layer 21 disposed on the surface of the negative electrode current collector 1 , a buffer layer 22 disposed on a side of the expansion layer 21 away from the negative electrode current collector 1 , and a protective layer 23 disposed on the buffer layer 22 away from the expansion layer 21 .

[0040] Different expansion layers 21, buffer layers 22 and protective layers 23 are arranged in the membrane layer 2, so that each layer can play its own role respectively, and the three cooperate to obtain a pole piece with higher capacity and smaller expansion, and specifically good electrochemical performance and cycle stability.

[0041] In some embodiments, the thickness of the membrane layer 2 is 0.035-0.95 mm, and the compaction density of the membrane layer 2 is 1.05-1.90 g / cm 3 The thickness of the membrane layer 2 changes with the thickness of the expansion layer 21, the buffer layer 22 and the protective layer 23. Preferably, the compaction density of the membrane layer 2 is 1.45-1.72 g / cm 3 .

[0042] In some embodiments, the diameters of the pores 24 of the expansion layer 21, the buffer layer 22 and the protective layer 23 satisfy the following relationship: 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 , K 膨胀层2150 ≤0.035mm, K 保护层 2350>0.

[0043] The expansion layer 21, the buffer layer 22 and the protective layer 23 all have pores 24, and the volume proportion of the pores 24 in the expansion layer 21, the buffer layer 22 and the protective layer 23 decreases successively, and the pores 24 become denser and denser successively. On the contrary, the diameters of the pores 24 in the protective layer 23, the buffer layer 22 and the expansion layer 21 become larger and larger. 膨胀层2150 is the diameter value of the pore 24 corresponding to the cumulative distribution percentage of all pores 24 in the expansion layer 21 reaching 50%, K 缓冲层2250 is the diameter value of the pore 24 corresponding to the cumulative distribution percentage of all pores 24 in the buffer layer 22 reaching 50%, K 保护层2350 It is the diameter value of the pore 24 corresponding to the cumulative distribution percentage of all the pores 24 in the protective layer 23 reaching 50%. The length unit of the diameter of the pore 24 can be selected from nm, μm, mm, cm, dm, and m according to the suitability of the description.

[0044] In some embodiments, the mass ratio of the silicon material 25 in the expansion layer 21, the buffer layer 22 and the protective layer 23 is 80% to 98%, the mass ratio of the gas-generating material in the expansion layer 21, the buffer layer 22 and the protective layer 23 is 0.1% to 5%, the mass ratio of the binder in the expansion layer 21, the buffer layer 22 and the protective layer 23 is 1% to 10%, and the mass ratio of the conductive agent in the expansion layer 21, the buffer layer 22 and the protective layer 23 is 0.2% to 8%.

[0045] In some embodiments, the content of the silicon material 25 in the expansion layer 21 is greater than the content of the silicon material 25 in the buffer layer 22 , and the content of the silicon material 25 in the buffer layer 22 is greater than the content of the silicon material 25 in the protection layer 23 .

[0046] Further, 35%≥the ratio of the mass of silicon in the expansion layer 21 to the mass of the expansion layer 21≥the ratio of the mass of silicon in the buffer layer 22 to the mass of the buffer layer 22≥the ratio of the mass of silicon in the protective layer 23 to the mass of the protective layer 23>0.5% or 85%≥the ratio of the mass of the silicon material 25 in the expansion layer 21 to the mass of the expansion layer 21≥the ratio of the mass of the silicon material 25 in the buffer layer 22 to the mass of the buffer layer 22≥the ratio of the mass of the silicon material 25 in the protective layer 23 to the mass of the protective layer 23>1.0%.

[0047] In some embodiments, the content of the gas generating material in the expansion layer 21 is greater than that in the buffer layer 22 and / or the content of the gas generating material in the expansion layer 21 is greater than that in the protective layer 23 .

[0048] In some embodiments, the binder content in the expansion layer 21 is greater than the binder content in the buffer layer 22 and / or the binder content in the protection layer 23 is greater than the binder content in the buffer layer 22 .

[0049] In some embodiments, the content of the conductive agent in the expansion layer 21 is greater than that in the buffer layer 22 and / or the content of the conductive agent in the expansion layer 21 is greater than that in the protective layer 23 .

[0050] 2. A method for preparing a negative electrode sheet, comprising the following steps:

[0051] Step S1, mixing the silicon material 25, the gas generating material, the binder and the conductive agent in a first ratio, adding a solvent and stirring to obtain a first negative electrode slurry;

[0052] Step S2, coating the first negative electrode slurry on at least one surface of the negative electrode current collector 1, and drying to form an expansion layer 21;

[0053] Step S3, mixing the silicon material 25, the gas generating material, the binder and the conductive agent in a second ratio, adding a solvent and stirring to obtain a second negative electrode slurry;

[0054] Step S4, coating the second negative electrode slurry on the surface of the expansion layer 21, and drying to form the buffer layer 22;

[0055] Step S5, mixing the silicon material 25, the gas generating material, the binder and the conductive agent in a third ratio, adding a solvent and stirring to obtain a third negative electrode slurry;

[0056] Step S6: coating the third negative electrode slurry on the surface of the buffer layer 22, drying to form a protective layer 23, and obtaining a negative electrode sheet.

[0057] A method for preparing a negative electrode sheet, wherein slurries with different silicon material 25 contents and gas-generating material contents are prepared respectively, and expansion layer 21, buffer layer 22 and protective layer 23 are obtained by coating respectively, and the preparation method is convenient and efficient. In the method for preparing a negative electrode sheet of the present invention, the drying temperature is 50°C to 120°C, and the drying time is 4 to 20 hours. The sheet pressing roller pressure is 0.05 to 0.55 MPa. Furthermore, the roller pressing pressure required for the first sheet pressing is less than the roller pressing pressure required for the subsequent two sheet pressings. The first ratio is the following raw materials by mass percentage: silicon material 2594% to 96%, binder 1.5% to 3%, conductive agent 1.5% to 1.8%, gas generating material 0.7% to 1.5%; the second ratio is the following raw materials by mass percentage: silicon material 2596% to 97%, binder 1.2% to 1.5%, conductive agent 1.1% to 1.5%, gas generating material 0.4% to 0.6%; the third ratio is the following raw materials by mass percentage: silicon material 2596% to 98%, binder 1.5% to 3%, conductive agent 0.6% to 0.8%, gas generating material 0.2% to 0.3%. The solvent is one of deionized water, purified water, and ultrapure water.

[0058] 3. A secondary battery with high capacity and cycle life, slow capacity decay and good cycle stability.

[0059] A secondary battery comprises the above-mentioned negative electrode plate.

[0060] Specifically, a secondary battery includes a positive electrode sheet, a separator, a negative electrode sheet, an electrolyte and a shell, wherein the separator is used to separate the positive electrode sheet and the negative electrode sheet, and the shell is used to encapsulate the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte, and the negative electrode sheet is the above-mentioned negative electrode sheet.

[0061] positive electrode

[0062] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b(wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5 O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be subjected to a modification treatment, and the method for modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification treatment may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current, and the positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.

[0063] Electrolyte

[0064] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0065] Preferably, the shell is made of stainless steel or aluminum-plastic film. More preferably, the shell is made of aluminum-plastic film.

[0066] Example 1

[0067] 1. Preparation of negative electrode sheet:

[0068] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0069] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0070] The drying temperature is 105° C. and the drying time is 6 hours.

[0071] The roller pressing pressure required for the first tableting was 0.09 MPa, and the roller pressing pressures required for the subsequent two tabletings were 1.65 MPa and 1.89 MPa respectively.

[0072] 1.3 The thickness of a membrane layer is 0.132 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the separator. Figure 1 As shown;

[0073] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.014m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0074] The silicon material 25 is a single particle or a composite particle. A single particle is obtained by mixing micron silicon oxide and a graphite composite material, and a plurality of single particles are aggregated to obtain a composite particle.

[0075] The mass of silicon material 25 in expansion layer 21, buffer layer 22 and protective layer 23 is 95.7%, 97% and 97.6% respectively, among which the mass of silicon oxide in each layer of expansion layer 21, buffer layer 22 and protective layer 23 accounts for 16.2%, 12.8% and 3.1% of the mass of expansion layer 21, buffer layer 22 and protective layer 23 respectively.

[0076] The binder is obtained by mixing polyacrylonitrile and styrene-butadiene latex in a mass ratio of 1:1, and the binder accounts for 1.5%, 1.2% and 1.5% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0077] The gas generating substance is ammonium fluoride, which accounts for 1.5%, 0.5% and 0.2% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0078] The conductive agent is obtained by mixing conductive carbon black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.8%, 1.2% and 0.6% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0079] 2 Preparation of lithium-ion batteries:

[0080] The silicon-containing layered negative electrode sheet, the separator, and the positive electrode sheet (containing 96.5% lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 The steps of winding the battery cell (O2 positive electrode active material) are performed, the battery cells are bundled with sealing films, the battery cells are installed in battery shells, the shell openings are welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging is performed, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0081] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0082] Example 2

[0083] 1. Preparation of negative electrode sheet:

[0084] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0085] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0086] The drying temperature is 105° C. and the drying time is 6 hours.

[0087] The roller pressing pressure required for the first tableting was 0.09 MPa, and the roller pressing pressures required for the subsequent two tabletings were 1.65 MPa and 1.89 MPa respectively.

[0088] 1.3 The thickness of one membrane is 0.136 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the separator;

[0089] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.014m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0090] The silicon material 25 is a single particle or a composite particle. A single particle is obtained by mixing micron silicon oxide and a graphite composite material, and a plurality of single particles are aggregated to obtain a composite particle.

[0091] The silicon material 25 accounts for 95.8%, 97.2% and 97% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively, wherein the mass of silicon oxide in the expansion layer 21, the buffer layer 22 and the protective layer 23 accounts for 15.8%, 12.7% and 2.9% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively.

[0092] The binder is obtained by mixing polyacrylonitrile and styrene-butadiene latex in a mass ratio of 1:1, and the binder accounts for 2.0%, 1.2% and 2.0% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0093] The gas-generating material is ammonium fluoride, which accounts for 0.7%, 0.4% and 0.2% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0094] The conductive agent is obtained by mixing conductive carbon black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.5%, 1.2% and 0.8% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0095] 2 Preparation of lithium-ion batteries:

[0096] The silicon-containing layered negative electrode sheet, isolation film, positive electrode sheet (containing 96.5% lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 The steps of winding the battery cell (O2 positive electrode active material) are performed, the battery cells are bundled with sealing films, the battery cells are installed in battery shells, the shell openings are welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging is performed, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0097] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0098] Example 3

[0099] 1 Silicon-containing layered negative electrode sheet:

[0100] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0101] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0102] The drying temperature is 105° C. and the drying time is 6 hours.

[0103] The roller pressing pressure required for the first tableting was 0.09 MPa, and the roller pressing pressures required for the subsequent two tabletings were 1.65 MPa and 1.89 MPa respectively.

[0104] 1.3 The thickness of one membrane is 0.137 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the isolation membrane;

[0105] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.014m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0106] The silicon material 25 is a single particle or a composite particle. A single particle is obtained by mixing micron silicon oxide and a graphite composite material, and a plurality of single particles are aggregated to obtain a composite particle.

[0107] The silicon material 25 accounts for 95.2%, 96.8% and 96.5% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively, wherein the mass of silicon oxide in the expansion layer 21, the buffer layer 22 and the protective layer 23 accounts for 15.5%, 12.7% and 2.8% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively.

[0108] The binder is obtained by mixing polyacrylonitrile and styrene-butadiene latex in a mass ratio of 1:1, and the binder accounts for 2.5%, 1.5% and 2.5% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0109] The gas generating material is ammonium fluoride, which accounts for 0.8%, 0.5% and 0.2% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0110] The conductive agent is obtained by mixing conductive carbon black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.8%, 1.2% and 0.6% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0111] 2 Preparation of lithium-ion batteries:

[0112] The silicon-containing layered negative electrode sheet, isolation film, positive electrode sheet (containing 96.5% lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 The steps of winding the battery cell (O2 positive electrode active material) are performed, the battery cells are bundled with sealing films, the battery cells are installed in battery shells, the shell openings are welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging is performed, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0113] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0114] Example 4

[0115] 1 Silicon-containing layered negative electrode sheet:

[0116] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0117] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0118] The drying temperature is 105° C. and the drying time is 6 hours.

[0119] The roller pressing pressure required for the first tableting was 0.09 MPa, and the roller pressing pressures required for the subsequent two tabletings were 1.65 MPa and 1.89 MPa respectively.

[0120] 1.3 The thickness of one membrane is 0.143 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the isolation membrane;

[0121] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.014m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0122] The silicon material 25 is a single particle or a composite particle. A single particle is obtained by mixing micron silicon oxide and a graphite composite material, and a plurality of single particles are aggregated to obtain a composite particle.

[0123] The silicon material 25 accounts for 94.7%, 96.8% and 96% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively, wherein the mass of silicon oxide in the expansion layer 21, the buffer layer 22 and the protective layer 23 accounts for 14.7%, 12.1% and 2.5% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively.

[0124] The binder is obtained by mixing polyacrylonitrile and styrene-butadiene latex in a mass ratio of 1:1, and the binder accounts for 3.0%, 1.5% and 3.0% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0125] The gas generating material is ammonium fluoride, which accounts for 0.8%, 0.5% and 0.2% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0126] The conductive agent is obtained by mixing conductive carbon black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.5%, 1.2% and 0.8% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0127] 2 Preparation of lithium-ion batteries:

[0128] The silicon-containing layered negative electrode sheet, isolation film, positive electrode sheet (containing 96.5% lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 The steps of winding the battery cell (O2 positive electrode active material) are performed, the battery cells are bundled with sealing films, the battery cells are installed in battery shells, the shell openings are welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging is performed, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0129] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0130] Example 5

[0131] 1 Silicon-containing layered negative electrode sheet:

[0132] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0133] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0134] The drying temperature is 85°C and the drying time is 12h.

[0135] The roller pressing pressure required for the first tableting was 0.13 MPa, and the roller pressing pressures required for the subsequent two tableting were 1.85 MPa and 1.95 MPa respectively.

[0136] 1.3 The thickness of one membrane is 0.119 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the isolation membrane;

[0137] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.018m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0138] The silicon material 25 is a single particle or a composite particle. The carbon-coated micron silicon material 25 is mixed with a graphite composite material to obtain a single particle, and a plurality of single particles are aggregated to obtain a composite particle.

[0139] The silicon material 25 accounts for 95.7%, 97% and 97.6% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively, wherein the mass of silicon oxide in the expansion layer 21, the buffer layer 22 and the protective layer 23 accounts for 15.6%, 12.4% and 3.0% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively.

[0140] The binder is obtained by mixing polyacrylonitrile and polyvinylidene fluoride in a mass ratio of 1:1, and the binder accounts for 1.5%, 1.2% and 1.5% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0141] The gas-generating material is ammonium fluoride, which accounts for 1%, 0.6% and 0.3% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0142] The conductive agent is obtained by mixing acetylene black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.8%, 1.2% and 0.6% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0143] Preparation of lithium-ion batteries:

[0144] The silicon-containing layered negative electrode sheet, the isolation film, and the positive electrode sheet (containing 96.5% of lithium iron phosphate LiFePO4 positive electrode active material) are wound to obtain a battery cell, the battery cell is sealed and bundled, the battery cell is installed in a battery shell, the shell opening is welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0145] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0146] Example 6

[0147] 1 Silicon-containing layered negative electrode sheet:

[0148] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0149] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0150] The drying temperature is 85° C. and the drying time is 12 h.

[0151] The roller pressing pressure required for the first tableting was 0.13 MPa, and the roller pressing pressures required for the subsequent two tabletings were 1.85 MPa and 1.95 MPa respectively.

[0152] 1.3 The thickness of one membrane is 0.117 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the isolation membrane;

[0153] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.018m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0154] The silicon material 25 is a single particle or a composite particle. A single particle is obtained by mixing micron silicon oxide and a graphite composite material, and a plurality of single particles are aggregated to obtain a composite particle.

[0155] The silicon material 25 accounts for 95.2%, 97% and 97.1% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively, wherein the mass of silicon oxide in the expansion layer 21, the buffer layer 22 and the protective layer 23 accounts for 15.5%, 12.5% ​​and 2.8% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively.

[0156] The binder is obtained by mixing polyacrylonitrile and polyvinylidene fluoride in a mass ratio of 1:1, and the binder accounts for 2%, 1.2% and 2% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0157] The gas-generating material is ammonium fluoride, which accounts for 1%, 0.6% and 0.3% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0158] The conductive agent is obtained by mixing acetylene black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.8%, 1.2% and 0.6% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0159] 2 Preparation of lithium-ion batteries:

[0160] The silicon-containing layered negative electrode sheet, the isolation film, and the positive electrode sheet (containing 96.5% of lithium iron phosphate LiFePO4 positive electrode active material) are wound to obtain a battery cell, the battery cell is sealed and bundled, the battery cell is installed in a battery shell, the shell opening is welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0161] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0162] Example 7

[0163] 1 Silicon-containing layered negative electrode sheet:

[0164] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0165] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0166] The drying temperature is 85° C. and the drying time is 12 h.

[0167] The roller pressing pressure required for the first tableting was 0.13 MPa, and the roller pressing pressures required for the subsequent two tabletings were 1.85 MPa and 1.95 MPa respectively.

[0168] 1.3 The thickness of one membrane is 0.127 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the isolation membrane;

[0169] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.018m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0170] The silicon material 25 is a single particle or a composite particle. A single particle is obtained by mixing micron silicon oxide and a graphite composite material, and a plurality of single particles are aggregated to obtain a composite particle.

[0171] The silicon material 25 accounts for 94.7%, 96.7% and 96.6% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively, wherein the mass of silicon oxide in the expansion layer 21, the buffer layer 22 and the protective layer 23 accounts for 15.3%, 12.2% and 2.5% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively.

[0172] The binder is obtained by mixing polyacrylonitrile and polyvinylidene fluoride in a mass ratio of 1:1, and the binder accounts for 2.5%, 1.5% and 2.5% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0173] The gas-generating material is ammonium fluoride, which accounts for 1%, 0.6% and 0.3% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0174] The conductive agent is obtained by mixing acetylene black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.8%, 1.2% and 0.6% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0175] 2 Preparation of lithium-ion batteries:

[0176] The silicon-containing layered negative electrode sheet, the isolation film, and the positive electrode sheet (containing 96.5% of lithium iron phosphate LiFePO4 positive electrode active material) are wound to obtain a battery cell, the battery cell is sealed and bundled, the battery cell is installed in a battery shell, the shell opening is welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0177] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0178] Embodiment 8:

[0179] 1 Silicon-containing layered negative electrode sheet:

[0180] 1.1 A silicon-containing layered negative electrode sheet, comprising a negative electrode current collector 1 copper foil and a film on each side of the copper foil, wherein the film comprises silicon material 25, a binder, and a conductive agent.

[0181] 1.2 A method for preparing a silicon-containing layered negative electrode sheet: silicon material 25, a conductive agent, a binder, and a gas-generating material are mixed, and then deionized water is added to stir and slurry to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21 and a buffer layer 22; the negative electrode slurry is coated on the copper foil again, pressed, sliced, and dried to obtain a copper foil with an attached expansion layer 21, a buffer layer 22 and a protective layer 23 (membrane), which is a silicon-containing layered negative electrode sheet.

[0182] The drying temperature is 85° C. and the drying time is 12 h.

[0183] The roller pressing pressure required for the first tableting was 0.13 MPa, and the roller pressing pressures required for the subsequent two tabletings were 1.85 MPa and 1.95 MPa respectively.

[0184] 1.3 The thickness of one membrane is 0.115 mm. The membrane includes an expansion layer 21, a buffer layer 22 and a protective layer 23. The expansion layer 21, the buffer layer 22 and the protective layer 23 are closely contacted and arranged in sequence, and the expansion layer 21 is closest to the negative electrode current collector 1, the buffer layer 22 and the protective layer 23 are away from the negative electrode current collector 1 in sequence, and the protective layer 23 is closest to the electrolyte and the isolation membrane;

[0185] The diameters of the pores 24 in the expansion layer 21, the buffer layer 22, and the protective layer 23 decrease in sequence, and the volume proportion of the pores 24 decreases in sequence. The pores 24 become denser in sequence, and the diameters of the pores 24 in the protective layer 23, the buffer layer 22, and the expansion layer 21 become sparser and larger in sequence, satisfying: 0.018m ≥ K 膨胀层2150 ≥K 缓冲层2250 ≥K 保护层2350 >0.

[0186] The silicon material 25 is a single particle or a composite particle. A single particle is obtained by mixing micron silicon oxide and a graphite composite material, and a plurality of single particles are aggregated to obtain a composite particle.

[0187] The silicon material 25 accounts for 94.2%, 96.7% and 96.1% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively. The mass of silicon oxide in the expansion layer 21, the buffer layer 22 and the protective layer 23 accounts for 15.1%, 12.1% and 2.3% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23, respectively.

[0188] The binder is obtained by mixing polyacrylonitrile and polyvinylidene fluoride in a mass ratio of 1:1, and the binder accounts for 3%, 1.5% and 3% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0189] The gas-generating material is ammonium fluoride, which accounts for 1%, 0.6% and 0.3% of the mass of the expansion layer 21, the buffer layer 22 and the protective layer 23 respectively;

[0190] The conductive agent is obtained by mixing acetylene black and conductive carbon nanotubes in a mass ratio of 8:2, and the conductive agent accounts for 1.8%, 1.2% and 0.6% of the mass of the expansion layer 21, the buffer layer 22 and the protection layer 23 respectively.

[0191] 2 Preparation of lithium-ion batteries:

[0192] The silicon-containing layered negative electrode sheet, the isolation film, and the positive electrode sheet (containing 96.5% of lithium iron phosphate LiFePO4 positive electrode active material) are wound to obtain a battery cell, the battery cell is sealed and bundled, the battery cell is installed in a battery shell, the shell opening is welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0193] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0194] Comparative Example 1:

[0195] 1. Preparation of silicon-containing negative electrode sheet:

[0196] 1.1 0.25 kg of micron silicon dioxide and 4.75 kg of graphite are mechanically stirred and mixed to obtain silicon material 25, a silicon-containing negative electrode sheet, and the preparation method of the negative electrode sheet is as follows: silicon material 25, a binder (the binder prepared in the above embodiment 2), and a conductive agent (the conductive agent prepared in the above embodiment 2) are mixed in a mass ratio of 96.5:2.5:1 to obtain a uniform slurry, the slurry is evenly coated on a copper foil, rolled at 1.89 MPa, sliced, and dried at 105°C for 6 hours to obtain a 0.128 mm thick layer of membrane, with a layer of membrane on each side of the silicon-containing negative electrode sheet.

[0197] 2 Preparation of lithium-ion batteries:

[0198] 2.1 Layer the silicon-containing negative electrode sheet, separator, and positive electrode sheet (containing 97.5% lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 The steps of winding the battery cell (O2 positive electrode active material) are performed, the battery cells are bundled with sealing films, the battery cells are installed in battery shells, the shell openings are welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging is performed, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0199] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0200] Comparative Example 2:

[0201] 1. Preparation of silicon-containing negative electrode sheet:

[0202] 1.1 0.25 kg of micron silicon dioxide and 4.75 kg of graphite are mechanically stirred and mixed to obtain silicon material 25, a silicon-containing negative electrode sheet, and the preparation method of the negative electrode sheet is as follows: silicon material 25, a binder (the binder prepared in the above embodiment 2), and a conductive agent (the conductive agent prepared in the above embodiment 2) are mixed in a mass ratio of 97:2.0:1.0 to obtain a uniform slurry, the slurry is evenly coated on a copper foil, rolled at 1.89 MPa, sliced, and dried at 105°C for 6 hours to obtain a 0.123 mm thick layer of membrane, with a layer of membrane on each side of the silicon-containing negative electrode sheet.

[0203] 2 Preparation of lithium-ion batteries:

[0204] 2.1 Layer the silicon-containing negative electrode sheet, separator, and positive electrode sheet (containing 97.5% lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 The steps of winding the battery cell (O2 positive electrode active material) are performed, the battery cells are bundled with sealing films, the battery cells are installed in battery shells, the shell openings are welded, vacuum drying is performed, the electrolyte is injected into the battery shell, packaging is performed, standing, forming, and capacity division are performed to obtain a lithium-ion battery.

[0205] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0206] Comparative Example 3

[0207] 1. Preparation of silicon-containing negative electrode sheet:

[0208] 1.1 0.15 kg of carbon-coated micron silicon material 25 and 4.85 kg of graphite are mechanically stirred and mixed to obtain silicon material 25, a silicon-containing negative electrode sheet, and the preparation method of the negative electrode sheet is as follows: silicon material 25, a binder (the binder prepared in the above embodiment 6), and a conductive agent (the conductive agent prepared in the above embodiment 6) are mixed in a mass ratio of 96.5:2.0:1.5 to obtain a uniform slurry, the slurry is evenly coated on a copper foil, rolled at 1.95 MPa, sliced, and dried at 85°C for 12 hours to obtain a 0.154 mm thick layer of membrane, and there is a layer of membrane on each side of the silicon-containing negative electrode sheet.

[0209] 2 Preparation of lithium-ion batteries:

[0210] 2.1 Wind the silicon-containing layered negative electrode sheet, the isolation film, and the positive electrode sheet (containing 97.5% lithium iron phosphate LiFePO4 positive electrode active material) to obtain a battery cell, seal the battery cell with a film, install the battery cell in a battery shell, weld the shell opening, vacuum dry, inject the electrolyte into the battery shell, package, stand, form, and divide the capacity to obtain a lithium-ion battery.

[0211] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0212] Comparative Example 4:

[0213] 1. Preparation of silicon-containing negative electrode sheet:

[0214] 1.1 0.15 kg of carbon-coated micron silicon material 25 and 4.85 kg of graphite are mechanically stirred and mixed to obtain silicon material 25, a silicon-containing negative electrode sheet, and the preparation method of the negative electrode sheet is as follows: silicon material 25, a binder (the binder prepared in the above embodiment 6), and a conductive agent (the conductive agent prepared in the above embodiment 6) are mixed in a mass ratio of 97:2.0:1.0 to obtain a uniform slurry, the slurry is evenly coated on a copper foil, rolled at 1.95 MPa, sliced, and dried at 85°C for 12 hours to obtain a 0.152 mm thick membrane sheet, with a membrane sheet on each side of the silicon-containing negative electrode sheet.

[0215] 2 Preparation of lithium-ion batteries:

[0216] 2.1 Wind the silicon-containing layered negative electrode sheet, the isolation film, and the positive electrode sheet (containing 97.5% lithium iron phosphate LiFePO4 positive electrode active material) to obtain a battery cell, seal the battery cell with a film, install the battery cell in a battery shell, weld the shell opening, vacuum dry, inject the electrolyte into the battery shell, package, stand, form, and divide the capacity to obtain a lithium-ion battery.

[0217] 3 The measurement items include: compaction density, and the capacity retention rate of the prepared lithium-ion battery after 1 cycle, 20 cycles, 100 cycles, 500 cycles, and 1000 cycles of charge and discharge, and the surface appearance of the membrane after 1000 cycles of charge and discharge is observed by electron microscope.

[0218] Table 1 Measurement data of Examples 1 to 8 and Comparative Examples 1 to 4

[0219]

[0220] When the membrane thickness and compaction density of Examples 1 to 8 and Comparative Examples 1 to 4 are similar, the capacity retention rates of the lithium ion batteries prepared by Examples 1 to 8 using the present invention at the 1st, 20th, 100th, 500th and 1000th cycles are significantly better than the capacity retention rates of the 1st, 20th, 100th, 500th and 1000th cycles of Comparative Examples 1 to 4. The appearance of the lithium ion battery membranes of Examples 1 to 8 is also better than that of the lithium ion battery membranes of Comparative Examples 1 to 4, indicating that Examples 1 to 8 have higher kinetic performance of lithium removal and lithium insertion, so that the lithium ion batteries have both higher first coulombic efficiency and better capacity retention rate.

[0221] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector and a membrane layer arranged on at least one surface of the negative electrode current collector, wherein the membrane layer comprises the following raw materials in parts by weight: 80 to 98 parts of silicon material, 0.1 to 5 parts of gas generating material, 1 to 10 parts of binder and 0.2 to 8 parts of conductive agent, wherein the membrane layer comprises an expansion layer arranged on the surface of the negative electrode current collector, a buffer layer arranged on the side of the expansion layer away from the negative electrode current collector and a protective layer arranged on the side of the buffer layer away from the expansion layer, and the pore diameters of the expansion layer, the buffer layer and the protective layer satisfy the following relationship: K 膨胀层50 >K 缓冲层50 >K 保护层50 , K 膨胀层50 ≤0.018mm, K 保护层50 >0, the mass ratio of silicon material in the expansion layer, buffer layer and protective layer is 80% to 98%, the mass ratio of gas-generating material in the expansion layer, buffer layer and protective layer is 0.1% to 5%, the mass ratio of binder in the expansion layer, buffer layer and protective layer is 1% to 10%, the content of silicon material in the expansion layer is greater than that in the buffer layer, the content of silicon material in the buffer layer is greater than that in the protective layer, the content of gas-generating material in the expansion layer is greater than that in the buffer layer and / or the content of gas-generating material in the expansion layer is greater than that in the protective layer, the content of binder in the expansion layer is greater than that in the buffer layer and / or the content of binder in the protective layer is greater than that in the buffer layer; K 膨胀层50 is the pore diameter value corresponding to the cumulative distribution percentage of all pores in the expansion layer reaching 50%, K 缓冲层50 is the pore diameter value corresponding to the cumulative distribution percentage of all pores in the buffer layer reaching 50%, K 保护层50 It is the pore diameter value corresponding to when the cumulative distribution percentage of all pores in the protective layer reaches 50%.

2. The negative electrode sheet according to claim 1, characterized in that: The thickness of the membrane layer is 0.035-0.95 mm, and the compaction density of the membrane layer is 1.05-1.90 g / cm 3 .

3. The negative electrode sheet according to claim 1, characterized in that: The mass proportion of the conductive agent in the expansion layer, the buffer layer and the protective layer is 0.2% to 8%.

4. The negative electrode sheet according to claim 3, characterized in that: The content of the conductive agent in the expansion layer is greater than that in the buffer layer and / or the content of the conductive agent in the expansion layer is greater than that in the protective layer.

5. A method for preparing a negative electrode sheet according to any one of claims 1 to 4, characterized in that: The steps include: Step S1, mixing silicon material, gas generating material, binder and conductive agent in a first ratio, adding solvent and stirring to obtain a first negative electrode slurry; Step S2, coating the first negative electrode slurry on at least one surface of the negative electrode current collector, and drying to form an expansion layer; Step S3, mixing the silicon material, the gas generating material, the binder and the conductive agent in a second ratio, adding a solvent and stirring to obtain a second negative electrode slurry; Step S4, coating the second negative electrode slurry on the surface of the expansion layer and drying to form a buffer layer; Step S5, mixing the silicon material, the gas generating material, the binder and the conductive agent in a third ratio, adding a solvent and stirring to obtain a third negative electrode slurry; Step S6: coating the third negative electrode slurry on the surface of the buffer layer, drying to form a protective layer, and obtaining a negative electrode sheet.

6. A secondary battery, characterized in that: The invention comprises the negative electrode sheet according to any one of claims 1 to 4.